HUBUNGAN ACADEMIC SELF-EFFICACY DENGAN ACADEMIC HOPELESSNESS PADA MAHASISWA SEMESTER AKHIR - Frans, Nathanael Darrel; Idulfilastri, Rita Markus (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Final-year students face a crucial phase fraught with academic pressure, which risks triggering Academic Hopelessness, a loss of hope regarding academic success. This study aims to examine the relationship between Academic Self-efficacy and Academic Hopelessness among final-year students. Using a non-experimental quantitative approach with convenience sampling, this study involved 219 active 7th and 8th-semester students in the Jabodetabek area. Data were collected using the Academic Hopelessness Inventory (AHI) and The Academic Self-efficacy Scale (TASES). Data analysis was performed using binary logistic regression and Spearman's rho correlation. The results showed a significant negative relationship between Academic Self-efficacy and Academic Hopelessness (p < 0.05). These findings indicate that the higher the students' self-confidence in their academic abilities, the lower their tendency to experience hopelessness. The research implications highlight the importance of strengthening self-efficacy as a protective factor for the mental health of final-year students. This finding is expected to serve as a reference for the development of preventive academic counseling services and psychological interventions in modern Indonesian higher education institutions. ABSTRAK Mahasiswa semester akhir menghadapi fase krusial yang sarat tekanan akademik, yang berisiko memicu Academic Hopelessness atau hilangnya harapan terhadap kesuksesan studi. Penelitian ini bertujuan untuk menguji hubungan antara Academic Self-efficacy dengan Academic Hopelessness pada mahasiswa semester akhir. Menggunakan pendekatan kuantitatif non-eksperimental dengan teknik convenience sampling, penelitian ini melibatkan 219 mahasiswa aktif semester 7 dan 8 di wilayah Jabodetabek. Pengumpulan data menggunakan Academic Hopelessness Inventory (AHI) dan The Academic Self-efficacy Scale (TASES). Analisis data dilakukan menggunakan uji regresi logistik biner dan korelasi Spearman’s rho. Hasil penelitian menunjukkan adanya hubungan negatif yang signifikan antara Academic Self-efficacy dan Academic Hopelessness (p < 0.05). Temuan ini mengindikasikan bahwa semakin tinggi keyakinan diri mahasiswa terhadap kemampuan akademiknya, semakin rendah kecenderungan mereka mengalami keputusasaan. Implikasi penelitian menyoroti pentingnya penguatan efikasi diri sebagai faktor protektif kesehatan mental mahasiswa tingkat akhir. Hasil ini diharapkan menjadi rujukan pengembangan layanan konseling akademik preventif dan intervensi psikologis di perguruan tinggi Indonesia saat ini modern.